Open sea mariculture of Asian seabass Lates calcarifer (Bloch, 1790) in marine floating cage at Balasore, Odisha, north-east coast of India - Mojjada, Suresh Kumar; Joseph, Imelda; Maheswarudu, G.; Ranjan, Ritesh; Dash, Biswajit; Gosh, S.; Syda Rao, G. (Indian Journal of Fisheries, 2012)
The present study was undertaken to evaluate the survival, growth rate and culture potential of sea bass, Lates calcarifer(Bloch, 1790) in an open sea floating cage at Balasore, Odisha in the north-east coast of India. A total number of 4357juveniles of L. calcarifer weighing on an average of 25 g were stocked in HDPE cylindrical open sea floating cage of 6 minner diameter with 6 m net bag depth in the middle of May, 2009. The fishes were fed @ 5-8 % of body weight thrice a daywith chopped trash fish throughout the experimental period and were harvested in the middle of November, 2009 after180 days of culture. Sea bass attained an average of 29.45 cm body length and 996.62 g in body weight at the time of harvest.Daily average increment in body length and body weight were 0.10 cm and 5.4 g respectively. Growth was allometric andaverage specific growth rate was 2.05. FCR was 1:6 and a survival rate of 79.6 % was recorded. The cost benefit ratio was0.5. Open sea floating cage culture of seabass was much more advantageous than culturing in inshore waters as evidencedfrom their growth performance and survival.